Laminate, packaging material, and packaging body
By using a specific laminated structure and material combination in the laminated body, including a highly birefringent intermediate layer and a polyvinyl base material layer, the gas barrier layer is formed, and the problems of single materialization and adhesion of the laminated body are solved, and good Environmental performance.
Patent Information
- Application Number
- CN202380050943.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to achieve single materialization, thinning and good bonding of each layer of the laminated body, resulting in the inability to reduce the environmental load.
The structure is sequentially laminated, including a base material layer, a first adhesive layer, an intermediate layer, a second adhesive layer and a sealing layer, wherein the base material layer, an intermediate layer and a sealing layer include polyethylene, birefringence of the intermediate layer ΔN is 0.01 or more, and a gas barrier layer is formed on the intermediate layer.
The laminated body has good adhesion and single materialization, which reduces the environmental load and improves the performance of the packaging material.
Smart Images

Figure CN119486880A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate and also to a packaging material and a packaging using the laminate.
[0002] This application claims priority based on Tokugan Application No. 2022-120464 filed in Japan on July 28, 2022, and Tokugan Application No. 2022-120350 filed in Japan on July 28, 2022, and the contents of which are incorporated herein by reference. Background Art
[0003] In recent years, due to the increasing awareness of environmental protection caused by the problem of marine plastic waste, there is a demand for more efficient recycling and classification of plastic materials. Packaging laminates, which have been used to achieve high performance by combining various types of materials, are no exception, and there is a demand for single-material laminates.
[0004] In order to realize a single material in a laminate, it is necessary to make the resin material constituting the film of each layer into the same system. For example, polyethylene, which is a kind of polyolefin, is widely used in packaging materials, and therefore, a single material laminate using polyethylene is expected.
[0005] In order to achieve single material, for example, Patent Document 1 proposes a laminate using a polyethylene film having a vapor-deposited layer on at least one surface of a substrate and a heat-seal layer, and discloses using stretched polyethylene as the substrate from the viewpoint of printability and bag-making suitability.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-055157 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In addition to being made of a single material, laminates are also required to be thinner and have good adhesion between layers as a component of packaging materials. If these conditions are not met, even a single material cannot be expected to be popularized and the environmental load cannot be reduced.
[0011] In view of the above circumstances, an object of the present invention is to provide a laminate having good adhesion and easily converted into a single material; and a packaging material and a packaging body using the laminate.
[0012] Means for solving problems
[0013] The present invention has the following aspects.
[0014] [1] A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealant layer laminated in this order, wherein the base layer, the intermediate layer, and the sealant layer contain polyethylene, and the intermediate layer has a birefringence ΔN of 0.01 or more.
[0015] [2] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in sequence, wherein the substrate layer, the intermediate layer, and the sealing layer comprise polyethylene, the birefringence ΔN of the intermediate layer is less than 0.01, and the difference between the maximum and minimum values of the line profile of the intermediate layer within a continuous range of 300 mm in one direction and the difference between the maximum and minimum values of the line profile within a continuous range of 300 mm in a direction orthogonal to the one direction are both less than 90 nm.
[0016] [3] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealant layer laminated in this order, wherein the substrate layer, the intermediate layer, and the sealant layer contain polyethylene, and the birefringence ΔN of the substrate layer is not less than 0.01.
[0017] [4] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in sequence, wherein the substrate layer, the intermediate layer, and the sealing layer comprise polyethylene, the birefringence ΔN of the substrate layer is less than 0.01, and the difference between the maximum value and the minimum value of the line profile of the substrate layer within a continuous range of 300 mm in one direction and the difference between the maximum value and the minimum value of the line profile within a continuous range of 300 mm in a direction orthogonal to the one direction are both less than 90 nm.
[0018] [5] The laminate according to any one of claims [1] to [4], further comprising a gas barrier layer formed on one surface of the intermediate layer.
[0019] [6] The laminate according to [5], wherein the gas barrier layer is composed of an inorganic oxide.
[0020] [7] The laminate according to [6], wherein the inorganic oxide includes any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.
[0021] [8] The laminate according to [5], further comprising a pretreatment layer provided between the intermediate layer and the gas barrier layer.
[0022] [9] The laminate according to [5], further comprising a covering layer covering the gas barrier layer.
[0023]
[10] A laminate according to [9], wherein the coating layer comprises any one of a metal alkoxide, a hydrolysis product of a metal alkoxide, and a water-soluble polymer; or any one of a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid.
[0024]
[11] The laminate according to any one of [1] to
[10] , wherein at least one of the first adhesive layer and the second adhesive layer is composed of a gas barrier adhesive.
[0025]
[12] The laminate according to any one of [1] to
[11] , wherein the polyethylene contained in the sealant layer is a low-density polyethylene or a linear low-density polyethylene.
[0026]
[13] The laminate according to any one of [1] to
[12] , wherein the proportion of the polyethylene in the laminate is 90% by mass or more.
[0027]
[14] A packaging material formed using the laminate according to any one of [1] to
[13] .
[0028]
[15] A packaging body comprising: the packaging material described in
[14] , and contents accommodated in the packaging material.
[0029] In one aspect, the present invention has the following aspects.
[0030] [A1] A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealant layer laminated in this order, wherein the base layer, the intermediate layer, and the sealant layer contain polyethylene, and the intermediate layer has a birefringence ΔN of not less than 0.01.
[0031] [A2] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in this order, wherein the substrate layer, the intermediate layer, and the sealing layer comprise polyethylene, the birefringence ΔN of the intermediate layer is less than 0.01, and the difference between the maximum value and the minimum value of the line profile of the intermediate layer within a continuous range of 300 mm in one direction and the difference between the maximum value and the minimum value of the line profile within a continuous range of 300 mm in a direction orthogonal to the one direction are both 90 nm or less.
[0032] [A3] The laminate according to [A1] or [A2], further comprising a gas barrier layer formed on one surface of the intermediate layer.
[0033] [A4] The laminate according to [A3], wherein the gas barrier layer is composed of an inorganic oxide.
[0034] [A5] The laminate according to [A4], wherein the inorganic oxide includes any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.
[0035] [A6] The laminate according to [A3], further comprising a pretreatment layer provided between the intermediate layer and the gas barrier layer.
[0036] [A7] The laminate according to [A3], further comprising a covering layer covering the gas barrier layer.
[0037] [A8] A laminate according to [A7], wherein the coating layer comprises any one of a metal alkoxide, a hydrolysis product of a metal alkoxide, and a water-soluble polymer; or any one of a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid.
[0038] [A9] The laminate according to any one of [A1] to [A8], wherein at least one of the first adhesive layer and the second adhesive layer is composed of a gas barrier adhesive.
[0039] [A10] The laminate according to any one of [A1] to [A9], wherein the polyethylene contained in the sealant layer is a low-density polyethylene or a linear low-density polyethylene.
[0040] [A11] The laminate according to any one of [A1] to [A10], wherein the proportion of the polyethylene in the laminate is 90% by mass or more.
[0041] [A12] A packaging material formed using the laminated body described in [A1] to [A11].
[0042] [A13] A packaging body comprising: the packaging material described in [A12], and contents accommodated in the packaging material.
[0043] As still another aspect, the present invention has the following aspects.
[0044] [B1] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealant layer laminated in this order, wherein the substrate layer, the intermediate layer, and the sealant layer contain polyethylene, and the birefringence ΔN of the substrate layer is not less than 0.01.
[0045] [B2] A laminate comprising a substrate layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in sequence, wherein the substrate layer, the intermediate layer, and the sealing layer comprise polyethylene, the birefringence ΔN of the substrate layer is less than 0.01, and the difference between the maximum value and the minimum value of the line profile of the substrate layer within a continuous range of 300 mm in one direction and the difference between the maximum value and the minimum value of the line profile within a continuous range of 300 mm in a direction orthogonal to the one direction are both less than 90 nm.
[0046] [B3] The laminate according to [B1] or [B2], further comprising a gas barrier layer formed on one surface of the intermediate layer.
[0047] [B4] The laminate according to [B3], wherein the gas barrier layer is composed of an inorganic oxide.
[0048] [B5] The laminate according to [B4], wherein the inorganic oxide includes any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.
[0049] [B6] The laminate according to [B3], further comprising a pretreatment layer provided between the intermediate layer and the gas barrier layer.
[0050] [B7] The laminate according to [B3], further comprising a covering layer covering the gas barrier layer.
[0051] [B8] A laminate according to [B7], wherein the coating layer comprises any one of a metal alkoxide, a hydrolysis product of a metal alkoxide, and a water-soluble polymer; or any one of a polycarboxylic acid polymer, a polyvalent metal compound, and a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid.
[0052] [B9] The laminate according to any one of [B1] to [B8], wherein at least one of the first adhesive layer and the second adhesive layer is composed of a gas barrier adhesive.
[0053] [B10] The laminate according to any one of [B1] to [B9], wherein the polyethylene contained in the sealant layer is a low-density polyethylene or a linear low-density polyethylene.
[0054] [B11] The laminate according to any one of [B1] to [B10], wherein the proportion of the polyethylene in the laminate is 90% by mass or more.
[0055] [B12] A packaging material formed using the laminated body described in [B1] to [B11].
[0056] [B13] A packaging body comprising: the packaging material described in [B12], and contents accommodated in the packaging material.
[0057] Effects of the Invention
[0058] According to the present invention, it is possible to provide a laminate having excellent adhesion and easily converted into a single material, and a packaging material and a packaging body using the laminate. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] [ Figure 1 ] is a schematic cross-sectional view of the stacked body involved in the first embodiment and the second embodiment of the present invention. DETAILED DESCRIPTION
[0060] <First Embodiment>
[0061] Below, refer to Figure 1 A first embodiment of the present invention will be described.
[0062] Figure 1 2 is a schematic cross-sectional view of a laminate 1 according to the present embodiment. The laminate 1 includes three layers: a base layer 10, an intermediate layer 30, and a sealant layer 50. These layers contain polyethylene as the largest resin component.
[0063] The base layer 10 and the intermediate layer 30 are bonded by the first adhesive layer 21, and the intermediate layer 30 and the sealing layer 50 are bonded by the second adhesive layer 22. That is, the laminate 1 is a laminate in which the base layer 10, the first adhesive layer 21, the intermediate layer 30, the second adhesive layer 22, and the sealing layer 50 are laminated in this order.
[0064] A gas barrier layer 60 is provided on the surface (on the surface) of the intermediate layer 30 on the sealant layer 50 side.
[0065] The polyethylene contained in the substrate layer 10, the intermediate layer 30, and the sealing layer 50 can be at least one polymer selected from a homopolymer, a random copolymer, and a block copolymer. A homopolymer is a polyethylene composed only of polyethylene monomers. A random copolymer is a polyethylene in which ethylene as the main monomer and a small amount of comonomers different from ethylene (such as α-olefins) are randomly copolymerized to form a homogeneous phase. A block copolymer is a polyethylene in which ethylene as the main monomer and the above-mentioned comonomers (such as α-olefins) are block copolymerized or polymerized into a rubbery state to form a heterogeneous phase.
[0066] There is no particular limitation on the density of the polyethylene contained in the substrate layer 10 and the intermediate layer 30, and any of high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-low-density polyethylene (VLDPE) can be used.
[0067] Here, high-density polyethylene has a density of 0.942 g / cm 3 The above polyethylene, medium density polyethylene has a density of 0.930g / cm 3 Above and less than 0.942g / cm 3 Low-density polyethylene has a density of 0.910 g / cm 3 Above and less than 0.930g / cm 3 The linear low-density polyethylene has a density of 0.910 g / cm 3 Above and less than 0.930cm 3 Ultra-low density polyethylene is a polyethylene with a density less than 0.910 g / cm 3 of polyethylene.
[0068] The density is a value obtained by a method in accordance with JIS K 7112: 1999. When the polyethylene contained in the sealant layer 50 in the largest amount is any one of LDPE, LLDPE, and VLDPE, the bonding property during heat fusion is improved, which is preferable.
[0069] The thickness of the base layer 10 is preferably in the range of 10 μm to 200 μm, more preferably in the range of 15 μm to 50 μm. When the base layer 10 is too thin, the strength of the laminate 1 tends to be insufficient. In addition, when the base layer 10 is too thick, the processing adaptability of the laminate 1 tends to decrease.
[0070] You may surface-treat one surface or both surfaces of the base material layer 10. By surface-treating, the adhesiveness with an adjacent layer can be improved.
[0071] The surface treatment method is not particularly limited. Examples of surface treatment include physical treatments such as corona discharge treatment, ozone treatment, low temperature plasma treatment using argon and / or oxygen and / or nitrogen (any one or more of argon, oxygen and nitrogen), and glow discharge treatment; and chemical treatments such as oxidation treatment using chemicals.
[0072] Although not an essential component of the laminate according to the present invention, the laminate according to the present embodiment includes the gas barrier layer 60 .
[0073] The gas barrier layer 60 is a single substance or a mixture having any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metal aluminum, and aluminum oxide as a main component, and exhibits barrier properties to a predetermined gas such as oxygen and water vapor. That is, the gas barrier layer 60 is composed of an inorganic oxide, and the inorganic oxide includes any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metal aluminum, and aluminum oxide.
[0074] The thickness of the gas barrier layer 60 varies depending on the type of components used, the composition and the film forming method, but can generally be appropriately set within the range of 3 to 300 nm. That is, the thickness of the gas barrier layer 60 is preferably within the range of 3 to 300 nm. When the thickness of the gas barrier layer 60 is less than 3 nm, sometimes a uniform film cannot be obtained or the film thickness is insufficient, and the function as a gas barrier layer may not be fully exerted. When the thickness of the gas barrier layer 60 exceeds 300 nm, cracks may occur in the gas barrier layer 60 due to external factors such as bending and stretching after film formation, and the barrier properties may be lost. The thickness of the gas barrier layer 60 is more preferably within the range of 6 to 150 nm.
[0075] There is no limitation on the method for forming the gas barrier layer 60, and for example, vacuum evaporation, plasma activated evaporation, ion beam evaporation, ion plating, sputtering, magnetron sputtering, or plasma chemical vapor deposition (PECVD) can be used. When these formation methods are combined with a plasma assisted method or an ion beam assisted method, the gas barrier layer 60 can be densely formed to improve the barrier properties.
[0076] In this embodiment, a pretreatment layer 61 is provided on the first surface 30a on the sealing layer 50 side of the intermediate layer 30, and the gas barrier layer 60 is formed thereon. The pretreatment layer 61 has an arbitrary structure and can be omitted, but by providing the pretreatment layer 61, the film forming property and the adhesion strength of the gas barrier layer 60 can be improved. There is no limitation on the composition and formation method of the pretreatment layer 61, and the composition of the pretreatment layer 61 can be selected from thermoplastic resins, thermosetting resins, ultraviolet curing resins, etc., and the formation method of the pretreatment layer 61 can be selected from plasma treatment, etc.
[0077] When a resin layer is used as the pretreatment layer 61, the content of the organic polymer in the pretreatment layer 61 may be, for example, 70% by mass or more, or 80% by mass or more. Examples of the organic polymer used in the pretreatment layer 61 include polyacrylic acid resin, polyester resin, polycarbonate resin, polyurethane resin, polyamide resin, polyolefin resin, polyimide resin, melamine resin, and phenolic resin. Considering the adhesion strength between the intermediate layer 30 and the gas barrier layer 60, it is preferred to include at least one of polyacrylic acid resin, polyol resin, polyurethane resin, polyamide resin, or a reaction product of these organic polymers. In addition, the pretreatment layer 61 may also include a silane coupling agent, an organic titanate, or a modified silicone oil.
[0078] As the organic polymer used in the pretreatment layer 61, further preferred examples include: an organic polymer having a carbamate bond generated by the reaction of a polyol having two or more hydroxyl groups at the polymer terminal and an isocyanate compound, and / or an organic polymer containing a reaction product of a polyol having two or more hydroxyl groups at the polymer terminal and an organic silane compound such as a silane coupling agent or its hydrolysis product.
[0079] As polyols, for example, at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol can be cited. Acrylic polyol can be obtained by polymerizing acrylic acid derivative monomers, or can be obtained by copolymerizing acrylic acid derivative monomers with other monomers. As acrylic acid derivative monomers, ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate can be cited. As monomers copolymerized with acrylic acid derivative monomers, styrene can be cited.
[0080] The isocyanate compound has the function of improving the adhesion between the intermediate layer 30 and the gas barrier layer 60 by utilizing the urethane bond generated by the reaction with the polyol. That is, the isocyanate compound functions as a crosslinking agent or a curing agent. As isocyanate compounds, for example, monomers such as aromatic toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI); aliphatic xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI) and isophorone diisocyanate (IPDI); their polymers; and their derivatives. The above-mentioned isocyanate compounds can be used alone or in combination of two or more.
[0081] Examples of the silane coupling agent include vinyl trimethoxysilane, γ-chloropropyl methyl dimethoxysilane, γ-chloropropyl trimethoxysilane, glycidoxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, and γ-methacryloxypropyl methyl dimethoxysilane. The organosilane compound may be a hydrolyzate of these silane coupling agents. The organosilane compound may contain one of the above-mentioned silane coupling agents and their hydrolyzates alone, or may contain two or more of them in combination.
[0082] The above components can be mixed in an organic solvent at any ratio to prepare a mixed solution, and the prepared mixed solution can be used to form a resin layer provided as the pretreatment layer 61 on the first surface 30a of the intermediate layer 30. The mixed solution can contain, for example, a curing accelerator such as a tertiary amine, an imidazole derivative, a metal salt compound of a carboxylic acid, a quaternary ammonium salt, and a quaternary phosphonium salt; an antioxidant such as a phenolic, sulfur-based, and phosphite-based antioxidant; a leveling agent; a flow regulator; a catalyst; a cross-linking reaction accelerator; and a filler.
[0083] The mixed solution can be applied to the first surface 30a of the intermediate layer 30 by a known printing method such as offset printing, gravure printing, or screen printing, or a known coating method such as roller coating, doctor blade coating, or gravure coating. After coating, the pretreatment layer 61 can be formed by, for example, heating to 50 to 200° C., drying and / or curing.
[0084] The thickness of the resin layer when forming the pretreatment layer 61 can be adjusted according to the application or the required characteristics, and is preferably 0.01 to 1 μm, and more preferably 0.01 to 0.5 μm. If the thickness of the pretreatment layer 61 is 0.01 μm or more, sufficient adhesion strength between the intermediate layer 30 and the gas barrier layer 60 can be obtained, and the gas barrier property also becomes good. If the thickness of the pretreatment layer 61 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing cost can be suppressed.
[0085] When the pretreatment layer 61 is formed by plasma treatment, it is preferred to use plasma treatment that can be performed in-line from the viewpoint of productivity. The plasma treatment method is not particularly limited to glow discharge, etc., and a magnet may be used to increase the plasma density. In addition, the gas used in the plasma treatment may be selected from any one or more of oxygen, nitrogen, and argon.
[0086] In this embodiment, the gas barrier layer 60 is covered by the coating layer 62. The coating layer 62 is an arbitrary structure and may be omitted (the coating layer 62 may not be provided). However, by providing the coating layer 62, the gas barrier layer 60 can be protected and the barrier properties of the laminate 1 can be further improved.
[0087] The coating layer 62 can be made of a thermoplastic resin, a thermosetting resin, an ultraviolet curing resin, a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, or a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound, i.e., a polyvalent metal salt of a carboxylic acid. A coating containing a metal alkoxide and a water-soluble polymer having excellent oxygen barrier properties is particularly preferred. The coating is formed using a coating agent having as a main agent an aqueous solution or a water / alcohol mixed solution containing a water-soluble polymer and one or more metal alkoxides or their hydrolyzates. For example, a coating agent is prepared by directly mixing a metal alkoxide with a solution obtained by dissolving a water-soluble polymer in an aqueous (water or water / alcohol mixed) solvent, or by mixing a product obtained by pre-hydrolyzing the metal alkoxide. The coating agent is applied to the gas barrier layer 60 and then dried, thereby forming the coating layer 62.
[0088] The components contained in the coating agent for forming the coating layer 62 are described in more detail. Examples of water-soluble polymers used in the coating agent include polyvinyl alcohol (PVA), polyvinyl pyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, and sodium alginate. In particular, when PVA is used, excellent gas barrier properties can be obtained, so it is preferred. PVA is generally obtained by saponifying polyvinyl acetate. As PVA, so-called partially saponified PVA in which several tens of acetic acid groups remain, or completely PVA in which only a few % of acetic acid groups remain can be used. A PVA in between the two can also be used.
[0089] The metal alkoxide used in the coating agent is a compound represented by the general formula M(OR)n (M: metal of Si, Al, R: alkyl such as CH3, C2H5). Specifically, tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum Al[OCH(CH3)2]3, etc. can be exemplified. As the silane coupling agent, compounds having an epoxy group such as 3-glycidyloxypropyltrimethoxysilane, compounds having an amino group such as 3-aminopropyltrimethoxysilane, compounds having a mercapto group such as 3-mercaptopropyltrimethoxysilane, compounds having an isocyanate group such as 3-isocyanatepropyltriethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate can be exemplified.
[0090] Polycarboxylic acid polymers are polymers having two or more carboxyl groups in the molecule. Examples of polycarboxylic acid polymers include: (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having carboxyl groups in molecules such as alginic acid, carboxymethyl cellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include: saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconic acid esters, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.
[0091] From the viewpoint of gas barrier properties, it is preferred to include a polymer containing a constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid and crotonic acid among the above-mentioned components, and it is particularly preferred to include a polymer containing a constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid and itaconic acid. In the above-mentioned polymer, the proportion of the constituent unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (wherein the total of all constituent units constituting the polymer is set to 100 mol%). The polymer may be a homopolymer or a copolymer. In the case where the polymer is a copolymer containing other constituent units other than the above-mentioned constituent units, as other constituent units, for example, constituent units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid, etc. can be listed.
[0092] The number average molecular weight of the polycarboxylic acid polymer is preferably in the range of 2,000 to 10,000,000, more preferably 5,000 to 1,000,000. When the number average molecular weight is less than 2,000, the water resistance of the gas barrier film is insufficient, the gas barrier property or transparency may be deteriorated by water, or whitening may occur, depending on the application. On the other hand, when the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent becomes high, which may impair the coating property. In the present embodiment, the number average molecular weight is a polystyrene-converted number average molecular weight obtained by gel permeation chromatography (GPC).
[0093] Various additives can be added to the coating agent with polycarboxylic acid polymer as the main component. Crosslinking agent, curing agent, leveling agent, defoaming agent, anti-blocking agent, antistatic agent, dispersant, surfactant, softener, stabilizer, film-forming agent and thickening agent can be added within the range that does not damage the barrier performance.
[0094] The solvent used in the coating agent with the polycarboxylic acid polymer as the main component is preferably an aqueous medium. As the aqueous medium, water, a water-soluble or hydrophilic organic solvent, or a mixture thereof can be listed. The aqueous medium is usually water, or contains water as the main component. The water content in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. As the water-soluble or hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; cellosolves; carbitols and nitriles such as acetonitrile, etc. can be listed.
[0095] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of a polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, and calcium carbonate. These can be used alone or in combination. From the perspective of the oxygen barrier properties of the oxygen barrier coating, the zinc oxide particles mentioned above are preferred. Zinc oxide is an inorganic material with ultraviolet absorption capability. The average particle size of the zinc oxide particles is not particularly limited, and from the perspective of gas barrier properties, transparency, and coating adaptability, the average particle size is preferably less than 5 μm, more preferably less than 1 μm, and particularly preferably less than 0.1 μm.
[0096] In the case of applying a coating agent with a polyvalent metal compound as the main component and drying it to form a coating, as required, in the range of not damaging the effect of the present embodiment, in addition to zinc oxide particles, various additives can also be contained in the coating agent. As this additive, it is possible to contain a resin that is soluble in or dispersible in the solvent used by the coating agent, a dispersant that is soluble in or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent and a tackifier, etc. Among the above, it is preferred to contain a resin that is soluble in or dispersible in the solvent used by the coating agent. Thus, the coating property and film-forming property of the coating agent are improved. As such a resin, for example, alkyd resin, melamine resin, acrylic resin, urethane resin, polyester resin, phenolic resin, amino resin, fluororesin, epoxy resin and isocyanate resin, etc. can be listed. In addition, it is preferred to contain a dispersant that is soluble in or dispersible in the solvent used by the coating agent. Thus, the dispersibility of the polyvalent metal compound is improved. As this dispersant, an anionic surfactant or a nonionic surfactant can be used. As the surfactant, various surfactants such as (poly) carboxylates, alkyl sulfate ester salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, alkyl phosphates, aromatic phosphates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, alkyl aryl sulfate ester salts, polyoxyethylene alkyl phosphates, sorbitan alkyl esters, glycerol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene alkyl aryl ethers, polyoxyethylene derivatives, polyoxyethylene sorbitan fatty acid esters, polyoxy fatty acid esters, and polyoxyethylene alkylamines can be cited. These surfactants can be used alone or in combination of two or more. When the coating agent containing a polyvalent metal compound as the main component contains an additive, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound: additive) is preferably in the range of 30:70 to 99:1, preferably in the range of 50:50 to 98:2.
[0097] As the solvent used in the coating agent with the polyvalent metal compound as the main component, for example, water, methanol, ethanol, isopropanol, n-propanol, n-butanol, n-pentanol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate can be listed. In addition, these solvents can be used alone or in combination of two or more. Among these, from the viewpoint of coating properties, methanol, ethanol, isopropanol, toluene, ethyl acetate, methyl ethyl ketone and water are preferred. In addition, from the viewpoint of manufacturability, methanol, ethanol, isopropanol and water are preferred.
[0098] In the case of forming a film of a polyvalent metal compound after applying a coating agent with a polycarboxylic acid polymer as the main component and drying it to form a film, the polycarboxylic acid polymer can also be preliminarily neutralized with a basic compound to form a part of the carboxyl group. By preliminarily neutralizing a part of the carboxyl group possessed by the polycarboxylic acid polymer, the water resistance and heat resistance of the film composed of the polycarboxylic acid polymer can be further improved. As the basic compound, it is preferred to select at least one basic compound from the group consisting of the above-mentioned polyvalent metal compound, a monovalent metal compound and ammonia. As the monovalent metal compound, for example, sodium hydroxide and potassium hydroxide can be listed.
[0099] When a coating agent mixed with a polycarboxylic acid polymer and a polyvalent metal compound is applied and dried to form a coating film, the coating agent is prepared by mixing a polycarboxylic acid polymer, a polyvalent metal compound, water or an alcohol as a solvent, a resin or a dispersant soluble or dispersible in the solvent, and an additive as required. The coating layer 62 can also be formed by applying such a coating agent using a known coating method and drying it.
[0100] As a coating method for the coating layer 62, for example, a casting method, a dipping method, a roll coating method, a gravure coating method, a screen printing method, a reverse coating method, a spray coating method, a sleeve coating method, a die coating method, a metering rod coating method, a chamber doctor blade coating method, and a curtain coating method can be used.
[0101] The thickness of the coating layer 62 varies depending on the composition of the coating agent used and the coating conditions, and is not particularly limited. However, when the coating layer 62 has a film thickness of less than 0.01 μm after drying, a uniform coating may not be formed, and sufficient gas barrier properties may not be obtained. When the coating layer 62 has a film thickness of more than 50 μm after drying, cracks are likely to occur in the coating layer 62. Therefore, the preferred thickness of the coating layer 62 is, for example, a thickness in the range of 0.01 to 50 μm, and the optimal thickness of the coating layer 62 is, for example, a thickness in the range of 0.1 to 10 μm.
[0102] A known dry lamination adhesive can be used as the first adhesive layer 21 and the second adhesive layer 22. Any dry lamination adhesive can be used without particular limitation, and specific examples thereof include two-component curing ester adhesives, ether adhesives, and urethane adhesives.
[0103] The gas barrier adhesive whose cured layer exhibits gas barrier properties can also be used for the first adhesive layer 21 and the second adhesive layer 22. By applying the gas barrier adhesive to the second adhesive layer 22, the gas barrier properties of the laminate 1 can be improved. The oxygen permeability of the cured layer of the gas barrier adhesive is preferably 150 cc / m 2 ·day·atm or less, more preferably 100cc / m 2·day·atm or less, more preferably 80cc / m 2 ·day·atm or less, particularly preferably 50cc / m 2 By setting the oxygen permeability within the above range, the gas barrier properties of the laminate can be sufficiently improved, and even if the gas barrier layer 60 or the coating layer 62 is slightly cracked, the gas barrier adhesive can enter the gap to replenish it, thereby suppressing the reduction of the gas barrier properties.
[0104] Gas barrier adhesives include epoxy adhesives, polyester / polyurethane adhesives, etc. Specific examples of gas barrier adhesives include "Maxive" manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC. and "Paslim" manufactured by DIC Corporation.
[0105] The thickness of the second adhesive layer 22 is preferably 0.1 to 20 μm, more preferably 0.5 to 10 μm, and further preferably 1 to 5 μm. By making the thickness of the second adhesive layer 22 greater than the lower limit of the above range, the rupture of the gas barrier layer 60 can be more fully suppressed, and the gas barrier properties of the laminate 1 as a whole can be further improved. In addition, by making the thickness of the second adhesive layer 22 greater than the lower limit of the above range, a buffering property that mitigates impact from the outside can be obtained, and the gas barrier layer 60 can be prevented from rupturing due to impact. On the other hand, by making the thickness of the second adhesive layer 22 less than the upper limit of the above range, the flexibility of the laminate 1 tends to be sufficiently maintained.
[0106] In addition to the above conditions, the thickness of the second adhesive layer 22 is preferably 50 times or more of the thickness of the gas barrier layer 60. By making the thickness of the second adhesive layer 22 satisfy the above conditions, the rupture of the gas barrier layer 60 and the coating layer 62 can be more fully suppressed, and when the gas barrier adhesive is used in the second adhesive layer 22, the gas barrier property of the entire laminate 1 can be further improved. In addition, by making the thickness of the second adhesive layer 22 satisfy the above conditions, the buffering property of mitigating the impact from the outside can be further improved, and the gas barrier layer 60 and the coating layer 62 can be prevented from rupturing due to the impact. On the other hand, from the perspective of maintaining the flexibility, processing adaptability, and cost of the laminate 1, the thickness of the second adhesive layer 22 is preferably 300 times or less of the thickness of the gas barrier layer 60.
[0107] The adhesive used to form the first adhesive layer 21 and the second adhesive layer 22 can be applied by, for example, a rod coating method, a dipping method, a roller coating method, a gravure coating method, a reverse coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, and a gravure offset printing method. The temperature when the adhesive coating is dried can be set to, for example, 30 to 200° C., preferably 50 to 180° C. In addition, the temperature when the coating is cured can be set to, for example, room temperature (27° C.) to 70° C., preferably 30 to 60° C. By setting the temperature during drying and curing to a temperature within the above range, cracks in the gas barrier layer 60 or the second adhesive layer 22 can be further suppressed, and excellent gas barrier properties can be exhibited.
[0108] The inventors have conducted various studies on a laminate having the above-mentioned basic structure in order to improve the adhesion of each layer, and have found a structure of an intermediate layer that can improve the adhesion with a base layer and a sealant layer.
[0109] First, it can be seen that when the birefringence ΔN of the intermediate layer is 0.01 or more, the adhesion with the adjacent substrate layer and the sealing layer becomes good. The birefringence ΔN is the absolute value of the difference Nx-Ny between the refractive index Nx of the resin layer in the MD direction and the refractive index Ny in the TD direction, and can be measured and calculated by the parallel Nicol rotation method, for example.
[0110] The MD direction and the TD direction are two mutually orthogonal directions defined in the resin film. Generally, in a resin film circulated in a roll state, its longitudinal direction is the MD direction and its width direction is the TD direction. In a resin film circulated in a rectangular or square shape, the direction in which one side extends is the MD direction, and the direction in which the other side orthogonal to the one side extends is the TD direction.
[0111] Generally, in a packaging material manufactured using a resin film, when the shape of the packaging material observed along the normal direction of the resin film is a rectangle or a square, the set of the MD direction and the TD direction determined in the above method is consistent with the set of the MD direction and the TD direction of the resin film used in the manufacturing. Therefore, when measuring the birefringence ΔN using such a packaging material, it is sufficient to measure and calculate the absolute value of the difference between the refractive index in the direction extending from one side and the refractive index in the direction extending from the other side orthogonal to the one side.
[0112] An example of a method for measuring birefringence ΔN is described below. A uniaxially polarized measurement light (wavelength 586.6 nm) is incident on the film from the normal direction of the film to be measured. The light transmitted through the film is decomposed into linear polarization in the MD direction and linear polarization in the TD direction, and the refractive index Nx and Ny of each linear polarization are measured. By taking the difference between Nx and Ny, the birefringence ΔN can be obtained.
[0113] Furthermore, it is understood that even if the birefringence ΔN of the intermediate layer is less than 0.01, when the in-plane phase profile of the intermediate layer is uniform, the adhesion with the adjacent layer is improved.
[0114] More specifically, it can be seen that when the difference between the maximum and minimum values of the two line contours, namely, the line contour for 300 mm in one direction along the surface of the intermediate layer and the line contour for 300 mm in a direction orthogonal to the one direction, is less than 90 nm, the adhesion with the substrate layer and the sealing layer can be improved.
[0115] The mechanism of the effect of the in-plane phase profile on adhesion is also partially unclear, but it is believed that the in-plane phase profile reflects the density of molecules in the film. In other words, it is confirmed that even if the thickness of the film is uniform, there will be deviations in the distribution of molecules in the thickness direction. As this deviation becomes larger, the film tends to be easily separated into the upper and lower sides in the middle of the thickness direction. Cohesion failure.
[0116] That is, even if the layer in contact with the intermediate layer is firmly bonded at the interface, if the in-plane phase profile of the intermediate layer does not satisfy the above conditions, cohesive failure of the intermediate layer occurs before interfacial delamination occurs, so the peel strength of the laminate becomes insufficient.
[0117] It should be noted that the inventors have confirmed in their research that when the birefringence ΔN is 0.01 or more, the improvement in close contact is not related to the state of the in-plane phase profile. This is believed to be because when the birefringence ΔN is 0.01 or more, the molecules in the resin layer are more bonded to each other, making it difficult for cohesive failure to occur.
[0118] The laminated body 1 according to the present embodiment can suppress cohesive failure of the intermediate layer and achieve good adhesion to either the base layer or the sealant layer by making the birefringence ΔN and the in-plane phase profile of the intermediate layer satisfy any of the above conditions.
[0119] Conventionally, in improving the adhesion of a laminate, much attention has been paid to the surface properties of the layer such as surface roughness. However, the present invention is groundbreaking in that it focuses on the internal structure of the layer to improve the adhesion.
[0120] The film stretching process also affects the in-plane phase profile of the resin film, but the inventors' research shows that in addition to the stretching process, various tensions acting on the film also affect the in-plane phase profile of the resin film. That is, it is impossible to fully predict whether the in-plane phase profile of a polyethylene film meets the above conditions based on whether the film is stretched or not, so actual measurement is required regardless of the stretching state.
[0121] The in-plane phase profile of the resin film can be measured using, for example, a measuring device "KAMAKIRI" manufactured by Photron Limited. In addition, in order to properly evaluate the in-plane phase profile, it is necessary to evaluate a certain degree of area range, so continuous measurements of more than 300 mm are required in two orthogonal directions. In the inventor's research, if it is more than 300 mm, the deviation of the measured value becomes less, so even if the measurement location is one, the in-plane phase profile can be stably measured, and it is also possible to perform continuous measurements of more than 300 mm at multiple locations and use the average value.
[0122] The two directions orthogonal to each other for measuring the line profile may be appropriately selected, but it is convenient to use the MD direction and TD direction described above. In this case, the MD direction and TD direction do not necessarily need to be accurately determined.
[0123] In the laminate 1 of the present embodiment having the above-mentioned structure, the adhesion of each layer constituting the laminate is good. The laminate 1 improves adhesion by suppressing the cohesive failure of the intermediate layer, so even if other layers such as a gas barrier layer exist between the adjacent resin layer, the adhesion improvement effect can be exerted without problem.
[0124] When two or one folded laminate 1 are heat-sealed at the peripheral portions while the sealant layers are facing each other, a packaging material such as a bag composed of the laminate 1 can be formed, and the package in which the contained content is sealed can be obtained.
[0125] The packaging material and the package body formed of the laminate 1 are easy to handle and easy to open. In addition, when the laminate 1 has the gas barrier layer 60, the contents can be prevented from contacting with water vapor or oxygen, and can be appropriately stored for a long period of time.
[0126] The laminate 1 can easily contain 90% by mass or more polyethylene by selecting appropriate polyethylene films as the base layer 10, the intermediate layer 30, and the sealant layer 50. That is, the laminate 1 can be easily made of a single material and can be easily recycled.
[0127] <Second Embodiment>
[0128] Next, a second embodiment of the present invention will be described, but the basic configuration is the same as that of the first embodiment. Therefore, the same configuration is denoted by the same reference numerals and the description thereof is omitted, and only the differences will be described.
[0129] The inventors have conducted various studies on a laminate having the above-mentioned basic structure in order to improve the adhesion of each layer, and have found a structure of a base material layer that can improve the adhesion with an intermediate layer.
[0130] First, it is known that when the birefringence ΔN of the substrate layer is 0.01 or more, the adhesion with the adjacent intermediate layer becomes good. The birefringence ΔN is the absolute value of the difference Nx-Ny between the refractive index Nx of the resin layer in the MD direction and the refractive index Ny in the TD direction, and can be measured and calculated by the parallel Nicol rotation method, for example.
[0131] Furthermore, it is understood that even when the birefringence ΔN of the base material layer is less than 0.01, when the in-plane phase profile of the base material layer is uniform, the adhesion with the adjacent intermediate layer is improved.
[0132] More specifically, it can be seen that when the difference between the maximum and minimum values of the two line contours, namely, the line contour for 300 mm in one direction along the surface of the substrate layer and the line contour for 300 mm in a direction orthogonal to the one direction, is less than 90 nm, the close adhesion with the intermediate layer can be achieved.
[0133] The mechanism of the effect of the in-plane phase profile on adhesion is also partially unclear, but it is believed that the in-plane phase profile reflects the density of molecules in the film. In other words, it is confirmed that even if the thickness of the film is uniform, there will be deviations in the distribution of molecules in the thickness direction. As this deviation becomes larger, the film tends to be easily separated into the upper and lower sides in the middle of the thickness direction. Cohesion failure.
[0134] That is, even if the substrate layer and the intermediate layer are firmly bonded at the interface, if the in-plane phase profile of the substrate layer does not satisfy the above conditions, cohesive failure of the substrate layer occurs before interfacial delamination occurs, so the peel strength of the laminate becomes insufficient.
[0135] It should be noted that the inventors have confirmed in their research that when the birefringence ΔN is 0.01 or more, the improvement in close contact is not related to the state of the in-plane phase profile. This is believed to be because when the birefringence ΔN is 0.01 or more, the molecules in the resin layer are more bonded to each other, making it difficult for cohesive failure to occur.
[0136] The laminated body 1 according to the present embodiment can suppress the cohesive failure of the base layer and achieve good adhesion to the intermediate layer by making the birefringence ΔN and the in-plane phase profile of the base layer satisfy any of the above conditions.
[0137] Conventionally, in improving the adhesion of a laminate, much attention has been paid to the surface properties of the layer such as surface roughness. However, the present invention is groundbreaking in that it focuses on the internal structure of the layer to improve the adhesion.
[0138] The film stretching process also affects the in-plane phase profile of the resin film, but the inventors' research shows that in addition to the stretching process, various tensions acting on the film also affect the in-plane phase profile of the resin film. That is, it is impossible to fully predict whether the in-plane phase profile of a polyethylene film meets the above conditions based on whether the film is stretched or not, so actual measurement is required regardless of the stretching state.
[0139] In the laminate 1 of the present embodiment having the above-mentioned structure, the base layer and the intermediate layer constituting the laminate have good adhesion. The laminate 1 improves adhesion by suppressing the cohesive failure of the base layer, so even if there are other layers such as a printing layer and a gas barrier layer between the base layer and the intermediate layer, the adhesion improvement effect can be exerted without problems.
[0140] When two or one folded laminate 1 are heat-sealed at the peripheral portions while the sealant layers are facing each other, a packaging material such as a bag composed of the laminate 1 can be formed, and the package in which the contained content is sealed can be obtained.
[0141] The packaging material and the package body formed of the laminate 1 are easy to handle and easy to open. In addition, when the laminate 1 has the gas barrier layer 60, the contents can be prevented from contacting with water vapor or oxygen, and can be appropriately stored for a long period of time.
[0142] The laminate 1 can easily contain 90% by mass or more polyethylene by selecting appropriate polyethylene films as the base layer 10, the intermediate layer 30, and the sealant layer 50. That is, the laminate 1 can be easily made of a single material and can be easily recycled.
[0143] The gas barrier film of the present invention will be further described using Examples and Comparative Examples. The technical scope of the present invention is not limited to the specific contents of Examples and Comparative Examples.
[0144] The thickness and density of the polyethylene films α1 to α6 used in Examples and Comparative Examples (Examples 1 to 14 and Comparative Examples 1 and 2 described later) are shown below.
[0145] α1: Thickness 32μm, density 0.950g / cm 3
[0146] α2: thickness 25 μm, density 0.940 g / cm 3
[0147] α3: thickness 35μm, density 0.948g / cm 3
[0148] α4: thickness 30 μm, density 0.947 g / cm 3
[0149] α5: thickness 35μm, density 0.926g / cm 3
[0150] α6: thickness 60 μm, density 0.921 g / cm 3
[0151] (Preparation of mixed solution for pretreatment layer)
[0152] Acrylic polyol and toluene diisocyanate were mixed so that the number of NCO groups of toluene diisocyanate was equal to the number of OH groups of acrylic polyol, and diluted with ethyl acetate so that the total solid content (the total amount of acrylic polyol and toluene diisocyanate) was 5% by mass. Furthermore, β-(3,4-epoxycyclohexyl)trimethoxysilane was added and mixed so that it was 5 parts by mass relative to 100 parts by mass of the total amount of acrylic polyol and toluene diisocyanate.
[0153] Through the above, a mixed solution for the pretreatment layer was obtained.
[0154] The first adhesive layer and the second adhesive layer may be any of the following.
[0155] (Urethane adhesive)
[0156] An adhesive prepared by mixing 11 parts by mass of Takenate A52 (manufactured by Mitsui Chemicals, Inc.) with 84 parts by mass of ethyl acetate with 100 parts by mass of Takelac A525 (manufactured by Mitsui Chemicals, Inc.)
[0157] (Gas barrier adhesive)
[0158] An adhesive prepared by mixing 16 parts by mass of Maxive C93T (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC.) and 5 parts by mass of Maxive M-100 (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC.) with 23 parts by mass of a solvent obtained by mixing ethyl acetate and methanol at a mass ratio of 1:1 was prepared.
[0159] (Example 1)
[0160] The resin film α5 was used as the intermediate layer 30. On both sides of the intermediate layer 30, 100 W·sec / m 2 The plasma treatment using Ar gas was carried out with a treatment intensity of . The treatment intensity was calculated as follows.
[0161] Power density [W / m 2 ]=input power [W] / cathode area [m 2 ]
[0162] Processing time [sec] = electrode MD width [m] / processing speed [m / sec]
[0163] Treatment intensity = power density [W / m 2 ]×Processing time [sec]
[0164] A silicon oxide (SiO) is formed on one surface of the intermediate layer 30 by using a vacuum evaporation device using electron beam heating. x ) is formed into a gas barrier layer 60 (film thickness 30 nm).
[0165] A gas barrier adhesive is applied on the gas barrier layer 60 to form a second adhesive layer 22 having a thickness of 3 μm, and the resin film α6 is attached as a sealing layer 50 .
[0166] A urethane adhesive was applied to the other surface of the intermediate layer 30 by gravure coating and dried to form a first adhesive layer 21 having a thickness of 3 μm, and the resin film α1 was attached by dry lamination to provide the base layer 10. Then, the laminate according to Example 1 was prepared by aging at 40°C for 4 days.
[0167] (Example 2)
[0168] A laminate according to Example 2 was produced in the same manner as in Example 1 except that the film thickness of the gas barrier layer 60 was set to 10 nm.
[0169] (Example 3)
[0170] By gravure coating method, 0.1g / m 2 The pretreatment layer mixture was applied on one surface of the intermediate layer 30 in an amount of , and dried and cured to form a pretreatment layer, and a gas barrier layer with a thickness of 40 nm was formed on the pretreatment layer. Except for this, the laminated body according to Example 3 was prepared in the same manner as Example 1.
[0171] (Example 4)
[0172] A pretreatment layer was formed on one surface of the intermediate layer 30 without plasma treatment, and a 25 nm thick gas barrier layer was formed on the pretreatment layer. A laminate according to Example 4 was prepared in the same manner as Example 3 except for the above.
[0173] (Example 5)
[0174] A coating agent prepared by mixing the following liquids (1) and (2) at a weight ratio of 6:4 was applied on the gas barrier layer 60 by gravure coating and dried to form a covering layer 62 having a thickness of 0.4 μm.
[0175] (1) Liquid: 89.6 g of hydrochloric acid (0.1 N) was added to 10.4 g of tetraethoxysilane and stirred for 30 minutes to hydrolyze the mixture to obtain a hydrolyzed solution with a solid content of 3 wt% (calculated as SiO2).
[0176] (2) Liquid: 3 wt% water / isopropanol solution of polyvinyl alcohol (water:isopropanol weight ratio 90:10)
[0177] A laminate according to Example 5 was produced in the same manner as in Example 4 except that the second adhesive layer 22 composed of a urethane adhesive was formed on the covering layer 62 and the sealing layer 50 was attached and the thickness of the gas barrier layer 60 was set to 28 nm.
[0178] (Example 6)
[0179] In addition to the gas barrier layer 60 being made of aluminum oxide (AlO x ) layer (formed by electron beam evaporation), a laminate according to Example 6 was produced in the same manner as in Example 1.
[0180] (Example 7)
[0181] In addition to the gas barrier layer 60 being made of aluminum oxide (AlO x ) layer (formed by electron beam evaporation), a laminate according to Example 7 was produced in the same manner as in Example 5.
[0182] (Example 8)
[0183] A laminate according to Example 8 was produced in the same manner as in Example 1, except that the gas barrier layer 60 was a metal aluminum (Al) layer having a thickness of 10 nm (formed by electron beam deposition).
[0184] (Example 9)
[0185] A laminate according to Example 9 was produced in the same manner as in Example 1, except that the gas barrier layer 60 was a metal aluminum (Al) layer (formed by electron beam deposition) having a film thickness of 50 nm.
[0186] (Example 10)
[0187] Hexamethyldisiloxane (HMDSO) was introduced into the vacuum device, and carbon-containing silicon oxide (SiO x C y ) was formed into a gas barrier layer 60 (film thickness 30 nm), and the same steps as in Example 1 were followed to produce a laminated body according to Example 10.
[0188] (Example 11)
[0189] In a vacuum device, monosilane (SiH4), ammonia (NH3) and nitrogen (N2) are introduced to form silicon nitride (SiN) by plasma CVD. x ) was formed into a gas barrier layer 60 (film thickness 30 nm), and the same steps as in Example 1 were followed to produce a laminated body according to Example 11.
[0190] (Example 12)
[0191] A laminate according to Example 12 was produced in the same manner as in Example 1 except that α2 was used as the base material layer 10 .
[0192] (Example 13)
[0193] A laminate according to Example 13 was produced in the same manner as in Example 1 except that α1 was used as the intermediate layer 30 .
[0194] (Example 14)
[0195] A laminated body according to Example 14 was produced in the same manner as in Example 1 except that α2 was used as the intermediate layer 30 .
[0196] (Comparative Example 1)
[0197] A laminate according to Comparative Example 1 was produced in the same manner as in Example 1 except that α3 was used as the intermediate layer 30 .
[0198] (Comparative Example 2)
[0199] A laminate according to Comparative Example 1 was produced in the same manner as in Example 1 except that α4 was used as the intermediate layer 30 .
[0200] The laminated bodies according to Examples 1 to 14 and Comparative Examples 1 and 2 were evaluated as follows.
[0201] (Measurement of In-Plane Phase Difference)
[0202] The in-plane phase of a film with a length of 300 mm or more was measured using KAMAKIRI (Photron Limited). Then, line profile analysis was performed in the MD direction and the TD direction. The (maximum value - minimum value) of the performed line profile analysis was calculated for both MD and TD.
[0203] (Birefringence ΔN)
[0204] The measurement conditions and the like related to the calculation of the birefringence ΔN are as follows.
[0205] Device: Phase difference measuring device (manufactured by Oji Scientific Instruments Co., Ltd.: KOBRA-WR)
[0206] Light source wavelength: 586.6nm
[0207] Measurement method: Parallel Nicol rotation method, measured directly above
[0208] (Adhesion Evaluation)
[0209] According to JIS Z1707, a 15 mm wide strip test piece was cut from the laminate of each example, and the lamination strength between the intermediate layer and the sealing layer was measured using a Tensilon universal testing machine RTC-1250 manufactured by ORIENTEC Co. LTD. The test piece with a lamination strength of 2N / 15mm or more, or the test piece in which the laminate was stretched and the intermediate layer and the sealing layer could not be peeled off was regarded as having good adhesion (0), and the test piece with a lamination strength of 2N / 15mm or less was regarded as having poor adhesion (×).
[0210] The main configuration and evaluation results of each example are shown in Table 1. Regarding the difference between the maximum value and the minimum value of the in-plane phase profile, the larger value between the MD direction and the TD direction is described.
[0211] [Table 1]
[0212]
[0213] In Examples 1 to 14, since the birefringence ΔN and the in-plane phase profile of the intermediate layer satisfy any one of the above conditions, good adhesion is exhibited.
[0214] On the other hand, in Comparative Examples 1 and 2, the birefringence ΔN and the in-plane phase profile of the intermediate layer did not satisfy the above conditions, and the adhesion was poor. In the test pieces of Comparative Examples 1 and 2, cohesive failure of the intermediate layer was observed.
[0215] The gas barrier film of the present invention will be further described using other examples and other comparative examples. The technical scope of the present invention is not limited to the specific contents of other examples and other comparative examples.
[0216] The thickness and density of the polyethylene films α1 to α6 used in other examples and other comparative examples (Examples 2-1 to 2-12 and Comparative Examples 2-1 to 2-2 described later) are shown below.
[0217] α1: Thickness 32μm, density 0.950g / cm 3
[0218] α2: thickness 25 μm, density 0.940 g / cm 3
[0219] α3: thickness 35μm, density 0.948g / cm 3
[0220] α4: thickness 30 μm, density 0.947 g / cm 3
[0221] α5: thickness 35μm, density 0.926g / cm 3
[0222] α6: thickness 60 μm, density 0.921 g / cm 3
[0223] (Preparation of mixed solution for pretreatment layer)
[0224] Acrylic polyol and toluene diisocyanate were mixed so that the number of NCO groups of toluene diisocyanate was equal to the number of OH groups of acrylic polyol, and diluted with ethyl acetate so that the total solid content (the total amount of acrylic polyol and toluene diisocyanate) was 5% by mass. Furthermore, β-(3,4-epoxycyclohexyl)trimethoxysilane was added and mixed so that it was 5 parts by mass relative to 100 parts by mass of the total amount of acrylic polyol and toluene diisocyanate.
[0225] Through the above, a mixed solution for the pretreatment layer was obtained.
[0226] The first adhesive layer and the second adhesive layer may be any of the following.
[0227] (Urethane adhesive)
[0228] An adhesive prepared by mixing 11 parts by mass of Takenate A52 (manufactured by Mitsui Chemicals, Inc.) with 84 parts by mass of ethyl acetate with 100 parts by mass of Takelac A525 (manufactured by Mitsui Chemicals, Inc.)
[0229] (Gas barrier adhesive)
[0230] An adhesive prepared by mixing 16 parts by mass of Maxive C93T (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC.) and 5 parts by mass of Maxive M-100 (manufactured by MITSUBISHI GAS CHEMICAL COMPANY, INC.) with 23 parts by mass of a solvent obtained by mixing ethyl acetate and methanol at a mass ratio of 1:1 was prepared.
[0231] (Example 2-1)
[0232] The resin film α5 was used as the intermediate layer 30. On both sides of the intermediate layer 30, 100 W·sec / m 2The plasma treatment using Ar gas was carried out with a treatment intensity of . The treatment intensity was calculated as follows.
[0233] Power density [W / m 2 ]=input power [W] / cathode area [m 2 ]
[0234] Processing time [sec] = electrode MD width [m] / processing speed [m / sec]
[0235] Treatment intensity = power density [W / m 2 ]×Processing time [sec]
[0236] A silicon oxide (SiO) is formed on one surface of the intermediate layer 30 by using a vacuum evaporation device using electron beam heating. x ) is formed into a gas barrier layer 60 (film thickness 30 nm).
[0237] A gas barrier adhesive is applied on the gas barrier layer 60 to form a second adhesive layer 22 having a thickness of 3 μm, and the resin film α6 is attached as a sealing layer 50 .
[0238] A urethane adhesive was applied to the other surface of the intermediate layer 30 by gravure coating and dried to form a first adhesive layer 21 having a thickness of 3 μm, and the resin film α1 was attached by dry lamination to provide the base layer 10. Then, aging was performed at 40° C. for 4 days to produce a laminate according to Example 2-1.
[0239] (Example 2-2)
[0240] A laminate according to Example 2-2 was produced in the same manner as in Example 2-1, except that the film thickness of the gas barrier layer 60 was set to 10 nm.
[0241] (Example 2-3)
[0242] By gravure coating method, 0.1g / m 2 The pretreatment layer mixture was applied on one surface of the intermediate layer 30 in an amount of , and dried and cured to form a pretreatment layer, and a gas barrier layer with a thickness of 40 nm was formed on the pretreatment layer. In addition, the laminated body of Example 2-3 was prepared in the same manner as Example 2-1.
[0243] (Example 2-4)
[0244] A pretreatment layer was formed on one surface of the intermediate layer 30 without plasma treatment, and a 25 nm thick gas barrier layer was formed on the pretreatment layer. A laminate according to Example 2-4 was prepared in the same manner as Example 2-3 except for the above.
[0245] (Example 2-5)
[0246] A coating agent prepared by mixing the following liquids (1) and (2) at a weight ratio of 6:4 was applied on the gas barrier layer 60 by gravure coating and dried to form a covering layer 62 having a thickness of 0.4 μm.
[0247] (1) Liquid: 89.6 g of hydrochloric acid (0.1 N) was added to 10.4 g of tetraethoxysilane and stirred for 30 minutes to hydrolyze the mixture to obtain a hydrolyzed solution with a solid content of 3 wt% (calculated as SiO2).
[0248] (2) Liquid: 3 wt% water / isopropanol solution of polyvinyl alcohol (water:isopropanol weight ratio 90:10)
[0249] A laminate according to Example 2-5 was produced in the same manner as in Example 2-4 except that the second adhesive layer 22 made of a urethane adhesive was formed on the covering layer 62 and the sealing layer 50 was attached and the thickness of the gas barrier layer 60 was set to 28 nm.
[0250] (Example 2-6)
[0251] In addition to the gas barrier layer 60 being made of aluminum oxide (AlO x ) layer (formed by electron beam evaporation), a laminate according to Example 2-6 was produced in the same manner as in Example 2-1.
[0252] (Example 2-7)
[0253] In addition to the gas barrier layer 60 being made of aluminum oxide (AlO x ) layer (formed by electron beam evaporation), a laminate according to Example 2-7 was produced in the same manner as in Example 2-5.
[0254] (Example 2-8)
[0255] A laminate according to Example 2-8 was produced in the same manner as in Example 2-1, except that the gas barrier layer 60 was a metal aluminum (Al) layer having a thickness of 10 nm (formed by electron beam deposition).
[0256] (Example 2-9)
[0257] A laminate according to Example 2-9 was produced in the same manner as in Example 2-1, except that the gas barrier layer 60 was a metal aluminum (Al) layer (formed by electron beam deposition) having a film thickness of 50 nm.
[0258] (Example 2-10)
[0259] Hexamethyldisiloxane (HMDSO) was introduced into the vacuum device, and carbon-containing silicon oxide (SiO x C y ) was formed into a gas barrier layer 60 (film thickness 30 nm), and a laminated body according to Example 2-10 was prepared according to the same procedures as Example 2-1.
[0260] (Example 2-11)
[0261] In a vacuum device, monosilane (SiH4), ammonia (NH3) and nitrogen (N2) are introduced to form silicon nitride (SiN) by plasma CVD. x ) was formed into a gas barrier layer 60 (film thickness 30 nm), and a laminated body according to Example 2-11 was prepared according to the same procedures as Example 2-1.
[0262] (Example 2-12)
[0263] A laminate according to Example 2-12 was produced in the same manner as in Example 2-1 except that α2 was used as the base material layer 10 .
[0264] (Comparative Example 2-1)
[0265] A laminate according to Comparative Example 2-1 was produced in the same manner as in Example 2-1 except that α3 was used as the base material layer 10 .
[0266] (Comparative Example 2-2)
[0267] A laminate according to Comparative Example 2-2 was produced in the same manner as in Example 2-1 except that α4 was used as the base material layer 10 .
[0268] The following evaluations were performed on the laminated bodies according to Examples 2-1 to 2-12 and Comparative Examples 2-1 to 2-2.
[0269] (Measurement of In-Plane Phase Difference)
[0270] The in-plane phase of a film with a length of 300 mm or more was measured using KAMAKIRI (Photron Limited). Then, line profile analysis was performed in the MD direction and the TD direction. The (maximum value - minimum value) of the performed line profile analysis was calculated for both MD and TD.
[0271] (Birefringence ΔN)
[0272] The measurement conditions and the like related to the calculation of the birefringence ΔN are as follows.
[0273] Device: Phase difference measuring device (manufactured by Oji Scientific Instruments Co., Ltd.: KOBRA-WR)
[0274] Light source wavelength: 586.6nm
[0275] Measurement method: Parallel Nicol rotation method, measured directly above
[0276] (Adhesion Evaluation)
[0277] According to JIS Z1707, a 15 mm wide strip test piece was cut from the laminate of each example, and the lamination strength between the substrate layer and the intermediate layer was measured using a Tensilon universal testing machine RTC-1250 of ORIENTEC Co. LTD. The test piece with a lamination strength of 2N / 15mm or more, or the test piece with the laminate elongated and unable to peel off the substrate layer and the intermediate layer was set as good adhesion (0), and the test piece with a lamination strength of 2N / 15mm or less was set as poor adhesion (×).
[0278] The main configuration and evaluation results of each example are shown in Table 2. Regarding the difference between the maximum value and the minimum value of the in-plane phase profile, the larger value between the MD direction and the TD direction is described.
[0279] [Table 2]
[0280]
[0281] In Examples 2-1 to 2-12, since the birefringence ΔN and the in-plane phase profile of the base material layer satisfied any one of the above conditions, good adhesion was exhibited.
[0282] On the other hand, in Comparative Examples 2-1 and 2-2, the birefringence ΔN and the in-plane phase profile of the substrate layer did not satisfy the above conditions, and the adhesion was poor. Cohesive failure of the substrate layer was observed in the test pieces of Comparative Examples 2-1 and 2-2.
[0283] The above describes the various embodiments and examples of the present invention, but the specific configuration is not limited to these embodiments, and also includes changes and combinations of the configurations that do not deviate from the scope of the present invention. The following examples illustrate some changes, but these are not all, and other changes may also be made. These changes can be freely combined.
[0284] The substrate layer may be provided with a printed layer for displaying various information, image patterns, etc. related to the content. When a printed layer with transferred text, etc. is provided on the surface provided with the first adhesive layer, the user does not come into direct contact with the printed layer, and the display of the printed layer, etc. can be appropriately preserved for a long time.
[0285] The gas barrier layer may be provided on the second surface on the substrate layer side instead of the first surface on the sealant layer side. Alternatively, the gas barrier layer may be provided on both surfaces of the intermediate layer.
[0286] Explanation of symbols
[0287] 1 Laminated body
[0288] 10. Base material layer
[0289] 21 first adhesive layer
[0290] 22 second adhesive layer
[0291] 30 Middle Layer
[0292] 30a Page 1
[0293] 50 Sealing layer
[0294] 60 Gas barrier layer
[0295] 61 Preprocessing layer
[0296] 62 Coating
Claims
1. A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in this order, The substrate layer, the intermediate layer, and the sealing layer include polyethylene, The birefringence ΔN of the intermediate layer is greater than or equal to 0.
01.
2. A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in this order, The substrate layer, the intermediate layer, and the sealing layer include polyethylene, The birefringence ΔN of the intermediate layer is less than 0.01, The difference between the maximum and minimum values of the line profile of the intermediate layer in a continuous range of 300 mm in one direction and the difference between the maximum and minimum values of the line profile in a continuous range of 300 mm in a direction orthogonal to the one direction are both 90 nm or less.
3. A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in this order, The substrate layer, the intermediate layer, and the sealing layer include polyethylene, The birefringence ΔN of the substrate layer is 0.01 or more.
4. A laminate comprising a base layer, a first adhesive layer, an intermediate layer, a second adhesive layer, and a sealing layer laminated in this order, The substrate layer, the intermediate layer, and the sealing layer include polyethylene, The birefringence ΔN of the substrate layer is less than 0.01, The difference between the maximum and minimum values of the line profile of the substrate layer in a continuous range of 300 mm in one direction and the difference between the maximum and minimum values of the line profile in a continuous range of 300 mm in a direction orthogonal to the one direction are both 90 nm or less.
5. The laminate according to any one of claims 1 to 4, The invention further comprises a gas barrier layer formed on one surface of the intermediate layer.
6. The laminate according to claim 5, wherein The gas barrier layer is composed of an inorganic oxide.
7. The laminate according to claim 6, wherein: The inorganic oxide includes any one of silicon oxide, carbon-containing silicon oxide, silicon nitride, metallic aluminum, and aluminum oxide.
8. The laminate according to claim 5, The invention further includes a pretreatment layer provided between the intermediate layer and the gas barrier layer.
9. The laminate according to claim 5, The invention further comprises a coating layer covering the gas barrier layer.
10. The laminate according to claim 9, wherein The coating layer includes any one of metal alkoxide, hydrolyzate of metal alkoxide, and water-soluble polymer; or any one of polycarboxylic acid polymer, polyvalent metal compound, and polyvalent metal salt of carboxylic acid which is a reaction product of polycarboxylic acid polymer and polyvalent metal compound.
11. The laminate according to any one of claims 1 to 4, wherein At least one of the first adhesive layer and the second adhesive layer is made of a gas barrier adhesive.
12. The laminate according to any one of claims 1 to 4, wherein The polyethylene contained in the sealant layer is low-density polyethylene or linear low-density polyethylene.
13. The laminate according to any one of claims 1 to 4, wherein The ratio of the polyethylene in the laminate is 90% by mass or more. 14 . A packaging material formed using the laminate according to claim 1 .
15. A packaging body, comprising: The packaging material according to claim 14, and The contents contained in the packaging material.
Citation Information
Patent Citations
Laminate, packaging material, packaging bag and stand pouch
JP2020055157A
Power supply for driving liquid crystal dimmer
JP2022120350A
Method for producing metal mask
JP2022120464A
Laminated porous polyolefin film and its production
JP1998100344A
Porous film
JP2007238822A